STUDI TENTANG INTERVENSI ETIKA DAN PENINGKATAN MORAL MAHASISWA - Najmudin, Najmudin; Adawiyah, Wiwiek Rabiatul (Faculty of Economics and Business Universitas Jenderal Soedirman, 2012)
This research is entitled ?Ethical Intervention and Moral Development ofStudents?. The purpose of the study is to compare the moral development of studentsfrom Accounting Departments with students of other departments at Economic FacultyUnsoed. The instrument used to measure the moral development of business studentswas defining issue test (DIT). Research findings indicate that students who haveattended ethical class have better moral development as compared to those who havenot taken the course. Moreover Accounting students have better moral development ascompared to students from other departments. Based on the findings, it isrecommended that ethics should be offered to business students since it appears toaffect students moral development. In addition, the inclusion of Ethics as a coursemust be offered to other departments too, as the case of accounting course. Lecturesshould provide simulation as a method of teaching in class in order to give betterimpact on students.